Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Kinerja Karyawan di Rumah Sakit Nur Hidayah Bantul - Hodiri Adi Putra; Nor Wijayanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Organizational culture and work environment are things that have the potential to affect employee performance. The good or bad service in a health institution, especially a hospital, is partly caused by the performance of employees who comply with work procedures, including the service culture in the organization and workplace. Objective: To determine whether there is an influence of organizational culture and work environment on employee performance at Nur Hidayah Hospital Bantul. Method: This research method is descriptive quantitative using a cross-sectional approach. The number of samples is 52 people who have permanent employee status. Results: The results of testing several variables with SPSS show that organizational culture has not been proven to have a significant effect on employee performance with a significant value (0.438> 0.05). The results of the analysis show that the work environment has a significant effect (0.000 <0.05). The results of the F test of the variables of organizational culture and work environment on employee performance at Nur Hidayah Hospital Bantul, obtained an F-count of 10,084 with a probability value of 0.000 <0.05 so that Ha is accepted. Conclusion: Organizational culture has not been proven to have a significant effect on performance. The work environment has a positive and significant effect on employee performance. Organizational culture variables and work environment variables simultaneously influence employee performance.